An Introduction to Health Psychology - Bennett Paul; Morrison Val (Pearson - Prentice Hall, 2006)
This book is a new and stimulating European textbook providing a valuable and engaging introduction to the field of Health Psychology. Preface, Acknowledgements, Being and Staying Healthy, What is Health?, Health Inequalities, Health - Risk Behaviour, Health - Enhancing Behaviour, Predicting Health Behaviour, Reducing Risk of Disease - Individual Approaches, Population Approaches to Public Health, Becoming Ill, The Body in Health and Illness, Symptom Perception and Interperception and Response, The Consultation and Beyond, Stress and Health and Illness: Theory, Stress and Illness Moderators, Managing Stress, Being Ill, The Impact of Illness on Quality of Life, The Impact of Illness on Patients and Their Families, Pain, Improving Health and Quality of Life, Futures, Glossary, References, Index.